The Role of Interest Groups in Improving the Quality of Public Policy (Case Study of Minimum Wage Policy in South Sulawesi Province) - Muhammad Rusdi (International Journal Labs, 2023)
The issue of the provincial minimum wage has always been confronted with the interests of who is excluded from a number of directly related interest groups. Trade union groups highlighted issues related to the minimum wage, namely around the issue of increasing nominal wages in relation to decent living conditions every year experiencing an increase in the inflation index. On the other hand, employer groups encourage the creation of business sustainability with minimal labor salary costs. These two issues always have conflicts in the process of determining the minimum wage policy of South Sulawesi Province regarding how interest groups contribute to the minimum wage policy. To answer these problems, argumentative qualitative research methods are used, focusing on the role of interest groups (Trade Union Groups and Employer Groups) in encouraging the formation of quality minimum wage policies, acceptable to all parties. The case of the process of determining the minimum wage policy for South Sulawesi Province in 2022 carried out in the Wage Council forum is the focus and locus of this research. The interactive single case analysis method was used to analyze the data of interest group debates in the Wage Board forum. The results showed that the ability between interest groups in the process of formulating provincial minimum wage policies, tends to differ in exerting pressure and influence on the minimum wage policy posture. Employers tend to use the power of lobbying and negotiation processes in wage board forums, while union groups tend to use the media of demonstrations and intimidation of worker group members. The ability to negotiate in the Wage Council forum has a real impact on the acceptance of policy proposals by the South Sulawesi provincial government authorities. The cohesiveness of interest groups is observed to have a positive effect on the sustainability of the struggle for policy ideas in policy forums, where trade union groups are still fragmented compared to employer groups. In the end, the decision on the provincial minimum wage policy was decided by considering the majority of views of the employer group with an increase of about 6.9% from the previous year's minimum wage.